PROBLEMATIKA PENGGUNAAN LABORATORIUM BAHASA - Kurniawan, Iwan (English Education: Jurnal Tadris Bahasa Inggris, 2014)
The objectives of this research are to find out the problems that faced by the teachers in teaching and lab head in managing the language laboratory. This research also tried to seek information regarding the solution taken by teachers and lab manager to solve those problems. Subjects of this research consisted of English teachers and lab manager of MAN Model Bandar Lampung. Research findings reveal the following this: a. Teachers problems; equipment number is not enough with students` number, majority teachers are not professional in using lab equipments, majority teachers only using lab for teaching listening, there are a few teachers do not know lab equipments name, nor they vary teaching activities. b. Lab manager`s problem; he found difficulties in searching new lab teaching materials, lab equipments are not adequate with students number, lab manager did not give orientation for teachers and students, and he also did not have lab technician to fix broken equipments. To overcome those problems, they read manual book of language lab use, split between fast and weak students in different groups, borrowing lab equipment and teaching materials from other schools, asking help from another school which has technician.